(untitled) (Research, Society and Development, 2025)
Antibiotics are natural or synthetic substances capable of eliminating or inhibiting the growth of pathogenic microorganisms that cause infections. Factors related to bacterial resistance increase the demand for new natural substances with antimicrobial action. In view of this, the aim of this study was to evaluate the antimicrobial potential of extracts obtained from Aspergillus niger OI3R1, previously isolated from soil in the state of Paraná (Brazil), as well as to carry out a qualitative analysis of its secondary metabolites. The extracts were produced in semi-solid rice and oat media with soybean straw and tested using the agar diffusion method against Escherichia coli and Pseudomonas aeruginosa, as well as carrying out chemical profile analyses using thin layer chromatography (TLC) to characterize the components of the extracts and fractions obtained by partitioning with solvents of increasing polarity. The ethyl acetate (Fr AcOEt) and dichloromethane (Fr CH2Cl2) fractions of both extracts showed activity against Pseudomonas aeruginosa. The chromatographic results showed the presence of alkaloids, quinones, amines and other nitrogenous compounds, the main components possibly related to the biological activity.